2011
DOI: 10.1055/s-0031-1296915
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Comparative Bioavailability of Two Vinpocetine Tablet Formulations in Healthy Volunteers by Using the Metabolite Apovincaminic Acid as Pharmacokinetic Parameter

Abstract: The objective of this study was to evaluate the pharmacokinetics of apovincaminic acid, the main metabolite of vinpocetine ((3alpha, 16alpha) -eburnamenine-14-carboxylic acid ethyl ester, CAS 42971-09-5), and to assess the average bioequivalence of two immediate release formulations of 10 mg vinpocetine tablets in 24 healthy male volunteers. The relative bioavailability of the test (generic) product (Vimpocetina) with respect to the reference product was determined in a single dose, randomized, crossover study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The first 5 μL of the filtrates was discarded and the subsequent filtrates were collected. Then, an appropriate amount of the filtrate was diluted with acetonitrile and assayed by a validated HPLC with mass spectrometry (MS) detection method,29 details are described later.…”
Section: Methodsmentioning
confidence: 99%
“…The first 5 μL of the filtrates was discarded and the subsequent filtrates were collected. Then, an appropriate amount of the filtrate was diluted with acetonitrile and assayed by a validated HPLC with mass spectrometry (MS) detection method,29 details are described later.…”
Section: Methodsmentioning
confidence: 99%
“…All the volunteers were prohibited to take medicines, following a one week wash out period before the beginning of the present study. In this study, apovincaminic acid plasma concentrations were monitored, as suggested in the literature 34 . This choice was made in consideration of the fast metabolic conversion from vinpocetine to apovincaminic acid.…”
Section: In Vivo Absorption Studiesmentioning
confidence: 99%
“…The determination of apovincaminic acid concentration was performed using a previously published HPLC method 34 . The preparation of the samples for HPLC analysis was performed according to the method reported by Hasa et al 33 .…”
Section: In Vivo Absorption Studiesmentioning
confidence: 99%
“…Non-competitive inhibition of dextromethorphan metabolism (mediated by CYP2D6) was seen with a K i value of 26 µM ( Figure 4 ). It should also be noted that vinpocetine has been shown to have a very low oral bioavailability (6%) in humans with maximum plasma concentration (Cmax) value of 60 ng/mL [ 27 ]. Hence, it is highly unlikely that the inhibitory concentrations (IC 50 and K i ) observed in this study will be achieved in vivo to inhibit CYP3A4 and CYP2D6 and thus the possibility of CYP mediated drug interaction seems to be remote.…”
Section: Resultsmentioning
confidence: 99%